Small-Angle X-ray Scattering (SAXS) Used for the Identification of Nicomorphine Polymorphic Changes at the Early Stage to Avoid Varied Stability and Possible Side Effects - Nermina Malanovic; Giovanni Birarda; Simone Eder; Heidrun Gruber-Woelfler; Franz Reiter; Krunoslav Juraic; Aden Hodzic (MDPI AG, 2024)
In this paper, we present the identification of polymorphisms at an early stage, identified by applying non-standard methods such as SAXS. We provide an analytical approach to polymorphism in the quality/purity of an active pharmaceutical ingredient (API), supplied to a generic company by two different suppliers (i.e., manufacturers). Changes in thermodynamic polymorphism firstly become visible in traces in the larger crystal lattices, which are visible on the SAXS spectrum only using the logarithmic scale, as shown in the result figures. Hence, we are here on the trail of the beginning of a new polymorph in nicomorphine, whose crystal waviness at the early stage is visible only in the additional symmetrical peaks identified and calculated using SAXS, while the chemical analyses excluded all kinds of chemical impurities. The chemical and structural properties were studied using the following techniques: SAXS, WAXS, DSC, dissolution, Raman spectroscopy, and FTIR. Only the SAXS technique could identify crucial differences and calculate the additional signals related to giant crystals, whilst a standard method such as WAXS showed none, and nor did the chemical analyses, such as Raman spectroscopy and FT-IR. This means that due to water in crystallization (known in nicomorphine) or thermodynamic waviness, the formation of the new polymorph starts first in traces, which become visible at larger distances from the crystal lattice, detectible only in the SAXS range. This is a very important premise and hypothesis for further research, and we believe that this work lays a new stone in understanding the origin of new unknown polymorphs and their mixtures. Therefore, the aim of this work is to show that the use of non-standard methods (i.e., SAXS) can be of great benefit to API analysis and the identification of polymorphic changes in the early phase, which can cause varied stability, solubility and bioavailability and thus different therapeutic effects or side effects.